Historiographical Analysis of Farag Fouda’s Thought in Kebenaran yang Hilang - Haukil Hannan; Akhmad Najibul Khairi Syaie (Universitas Nahdlatul Ulama Surabaya, 2024)
Kebenaran yang Hilang (KYH), a historical work by Farag Fouda, has garnered significant criticism, especially from Islamist groups, due to its unconventional methodologies and Fouda’s lack of formal training as a historian. These critiques reflect broader debates in Islamic historiography regarding the boundaries of historical scholarship and who is deemed qualified to contribute to this discourse. This study addresses two central issues: the historiographical nature of KYH and its legitimacy as an Islamic historical text, particularly in its treatment of early Islamic political history. Through historiographical analysis, the research explores Fouda’s reliance on traditional sources, his historical methods, and his diachronic, liberal perspective. The analysis places KYH within the theoretical frameworks used by informal historians. Despite Fouda's non-traditional background, this study demonstrates that KYH meets key criteria for a valid historical work by integrating both traditional and modern historiographical approaches. The research introduces fresh perspectives on Islamic history, while simultaneously challenging established narratives. It contends that, despite its controversial reception, KYH holds significant value as a historical text and makes a meaningful contribution to the field of Islamic historiography, meriting further scholarly critique and engagement.